Use of Obstetric and Gynecologic Hospitalists Is Associated With Decreased Severe Maternal Morbidity in the United States. Issue 3 (9th April 2023) - Torbenson, Vanessa E.; Tatsis, Vasiliki; Bradley, Sarah L.; Butler, Jennifer; Kjerulff, Lucy; McLaughlin, G. Blake; Stika, Catherine S.; Tappin, Dyanne; VanBlaricom, Amy; Mehta, Ramila; Branda, Megan; McCue, Brigid
Abstract : Objectives: This study aimed to evaluate the prevalence of obstetric and gynecologic (Ob/Gyn) hospitalists and determine if an association exists between the presence of Ob/Gyn hospitalists and severe maternal morbidity (SMM). Methods: This observational study included data from hospitals listed in the USA TODAY 's 2019 article titled, "Deadly deliveries: Childbirth complication rates at maternity hospitals." Telephone and email surveys of staff in these hospitals identified the presence or absence of continuous providers in the hospital 24 hours, 7 days a week (24/7 coverage) and the types of providers who are employed, then compared these responses with the SMM cited by USA TODAY . Results: Eight hundred ten hospitals were contacted, with participation from 614 labor and delivery units for a response rate of 75.8%. Fifty-seven percent of units were staffed with 24/7 coverage, with 46% of hospitals' coverage primarily provided by an Ob/Gyn hospitalist and 54% primarily by a nonhospitalist OB/Gyn provider. The SMM and presence of 24/7 coverage increased with the level of neonatal care and delivery volume. Of hospitals with 24/7 coverage, those that primarily used Ob/Gyn hospitalists had a lower SMM for all mothers (1.7 versus 2.0, P = 0.014) and for low-income mothers (1.9 versus 2.30, P = 0.007) than those who primarily used nonhospitalist OB/Gyn providers. Conclusions: Severe maternal morbidity increases with delivery volume, level of neonatal care, and 24/7 coverage. Of hospitals with 24/7 coverage, units that staff with Ob/Gyn hospitalists have lower levels of SMM than those that use nonhospitalist Ob/Gyn providers.